Pengembangan Sistem Informasi Penjualan Barang Elektronik berbasis Website menggunakan Framework Laravel (Studi Kasus: UD Berkah Menuju Sukses Jombang) - Zidane Ramadhan Misbahuddin Najib; Buce Trias Hanggara; Widhy Hayuhardhika Nugraha Putra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2022)
UD Berkah Menuju Sukses is one of the MSMEs located in Jombang City, East Java. UD Berkah Menuju Sukses is engaged in the business process of selling electronic goods such as air conditioners, refrigerators, fans, and their respective spare - parts. In sales activities, ud Berkah Menuju Sukses only sells products directly through the store and is still said to be very simple, because customers who want to buy electronic goods still need the help of store employees to find out the details or specifications of electronic goods sold. The limitation of store employees in providing item details is an important problem because the goods sold, especially electronic spare parts, there are always updates from the supplier so that store employees must understand the details of the goods. To make it easier to sell electronic goods, a website-based electronic goods sales information system was developed using frawework laravel as the main builder so that later it can make it easier for customers to see and get detailed information on products sold because they do not have to come to the store to get the goods they want to buy. To build a website required planning needs to know the functional and non-functional needs of the system that is using UML diagrams and database design using Physical Data Model (PDM). The development of this system is done by using the Rapid Application Development (RAD) model, with PHP programming language, MySQL DBMS, and utilizing Bootstrap. Website testing is done by using blackbox testing with 100% valid results. Compatibility testing with the results there are no problems in the system with evidence of no Critical Issues, Major Issues, and Minor Issues. Usability testing was conducted on 7 respondents and obtained an average score of 82 with the conclusion ofâ€ ACCEPTABLE "in the Acceptability Range assessment, getting a B on the" GRADE SCALEâ€ and "EXCELLENT" on the Adjectvie Ratings aspect.